UNRWA's innovative e-Health for 5 million Palestine refugees in the Near East. Issue 3 (8th June 2018) - Ballout, Ghada; Al-Shorbaji, Najeeb; Abu-Kishk, Nada; Turki, Yassir; Zeidan, Wafaa; Seita, Akihiro
Abstract : The United Nations Relief and Works Agency for Palestine Refugees (UNRWA) provides primary healthcare (PHC) for some 5 million Palestine refugees in five operational fields (Jordan, Syria, Lebanon, West Bank and Gaza) through its 143 health centres (HCs). UNRWA started, in 2009, developing an electronic health records (e-Health) system. The primary aim was to improve the quality of services and to respond to the increasing workload and the rise in the prevalence of non-communicable diseases (NCDs). The system was developed in-house based on the Family Health Team approach as a web-based, patient-centred application to support UNRWA's health services for common illnesses, maternal and child health, NCDs, laboratory and pharmacy. It has a built-in appointment system, uses the International Statistical Classification of Diseases, 10 th Edition classification and generates 29 reports. By October 2017, the system was rolled out in 121 HCs, of which 100 are paperless, covering almost 3 million refugee population, and managing some 9 million visits a year. The number of physician's daily consultations was reduced from 104 to 85. It enabled the introduction of an innovative cohort analysis to monitor patients with NCD efficiently. 89% of doctors expressed their satisfaction concerning timesaving and efficiency of e-Health. Long-standing effective PHC services, detailed clinical guidelines, well-trained staff and in-house development made that roll-out possible. Interoperability enabled operation in five different fields. However, the main challenges include HCs' infrastructure and connectivity. UNRWA is working to address such challenges to complete the roll-out, except for HCs in Syria, by the end of 2017. UNRWA's experience indicates that implementing such an innovation is possible and can improve efficiency, effectiveness and control the duplication of PHC services. Mobile technologies (m-Health) and integration with host countries' e-Health systems are planned to achieve best value for low cost.